An entropy-regulated medium-high-entropy composite toughened gradient ceramic tool material, a preparation method and application thereof
Patent Information
- Application Number
- CN202611196683.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-16
AI Technical Summary
[0009]目前尚未发现通过熵调控策略将不同构型熵水平的中/高熵碳化物与双相高熵合金复合,构建中高熵复合强韧化的氧化铝梯度陶瓷刀具的相关研究
[0047] 1. This invention introduces entropy regulation strategy and gradient structure design into the alumina-based ceramic cutting tool material system, constructing a five-layer symmetrical gradient structure. The surface layer uses a pentagonal high-entropy carbide (HfNbTaTiZr)C with low thermal expansion coefficient and high hardness. During sintering and cooling, residual compressive stress is introduced into the surface layer due to the mismatch in thermal expansion coefficient, which can effectively inhibit the initiation and propagation of surface cracks. The middle layer uses a quaternary high-entropy carbide (HfTaZrTi)C with moderate performance to achieve a smooth transition in performance. The inner layer uses a ternary medium-entropy carbide (HfZrTi)C with high thermal expansion coefficient and relatively low hardness. Combined with the toughening effect of the AlCoCrFeNi pentagonal equiatomic ratio high-entropy alloy, the overall fracture toughness of the material is effectively improved. Through entropy regulation, the synergistic effect of the dual gradient design is achieved, realizing the simultaneous improvement of material hardness and toughness, i.e., medium-high entropy composite toughening.
Smart Images

Figure CN122918409A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic cutting tool materials technology, specifically relating to an alumina gradient ceramic cutting tool material that achieves medium-to-high entropy composite toughness through entropy regulation, its preparation method, and its application. Background Technology
[0002] Ceramic materials, due to their excellent high-temperature stability, chemical stability, and wear resistance, have broad application prospects in aerospace, machining, and energy chemical industries. However, the inherent brittleness of ceramics, leading to low fracture toughness, has long been a key bottleneck restricting the improvement of their structural reliability and engineering application. Although strategies such as particle dispersion toughening, whisker / fiber toughening, and phase transformation toughening have improved the toughness of ceramic materials to some extent, these methods are often accompanied by a significant decrease in hardness, making it difficult to achieve synergistic optimization of hardness and toughness. Therefore, exploring new toughening mechanisms and structural design concepts has become one of the core scientific issues in the field of high-performance structural ceramics research.
[0003] Functionally graded ceramics (FJCs) achieve differentiated performance advantages in different regions by allowing continuous or quasi-continuous variations in composition, microstructure, or phases in space. This effectively overcomes the dilemma of balancing hardness and toughness in traditional toughening methods, achieving a good balance between the two. For applications like ceramic cutting tools that operate under high-stress environments, the surface of the ceramic material inevitably experiences tensile stress induced by mechanical impact and friction during service, which becomes the main driving force for crack initiation and propagation.
[0004] Therefore, the design of gradient ceramics for this application must meet two criteria: First, the hardness should follow a gradient distribution principle that decreases from the surface to the interior. High surface hardness imparts excellent wear resistance to the material, while a suitable decrease in internal hardness is usually accompanied by an increase in toughness, which is beneficial for enhancing fracture energy absorption capacity. Second, the coefficient of thermal expansion should follow a distribution principle that increases from the surface to the interior. During the cooling process after preparation, this distribution can introduce beneficial residual compressive stress into the surface layer. This compressive stress can effectively offset the external tensile stress during service, thereby inhibiting crack initiation and propagation, and significantly improving the fracture toughness and damage tolerance of the ceramic material. The synergistic effect of the above two gradient distributions provides an effective way to simultaneously optimize the hardness and toughness of ceramic materials.
[0005] In the design of toughening phases for high-performance ceramic materials, high-entropy alloys have attracted widespread attention due to their excellent plastic deformation capabilities. However, existing research has largely focused on the development and performance characterization of high-entropy alloys themselves, with insufficient exploration of their application as toughening phases in ceramic matrix materials, especially gradient ceramic materials. Dual-phase high-entropy alloys, as a novel type of material with a composite microstructure, can provide ceramics with a unique and multifunctional toughening mechanism. AlCoCrFeNi dual-phase high-entropy alloys simultaneously contain face-centered cubic and body-centered cubic phases, which can serve as toughening phases in the ceramic matrix, absorbing fracture energy through crack deflection and bridging effects, thereby improving the overall toughness of the ceramic material.
[0006] Inspired by the concept of high-entropy alloys, entropy stabilization strategies have been successfully extended to the ceramics field, giving rise to medium-entropy carbides (≥3 types of metal cations) and high-entropy carbides (≥4 types of metal cations). These materials are composed of multiple main elements and exhibit superior properties that are difficult to achieve with traditional binary carbides, including high hardness, good wear resistance, and excellent oxidation resistance. Among the many high-entropy carbide systems, the carbide system containing five refractory elements (Hf-Nb-Ta-Ti-Zr-C system) is considered a highly promising candidate material for ceramic reinforcing phases due to the extremely high melting points and high hardness of each component carbide.
[0007] However, current research on medium / high entropy carbides as reinforcing phases in ceramics mainly focuses on single homogeneous materials, and their systematic application in gradient structures has not yet been reported. In particular, the differences in hardness and coefficient of thermal expansion between medium / high entropy carbides with different configurational entropy levels (ternary, quaternary, and pentaneous) have not been used in the structural design of gradient ceramics. The coefficient of thermal expansion, as a core parameter in gradient ceramic design, and its variation with elemental composition and configurational entropy level, is an important basis for constructing gradient structures based on the principle of matching coefficients of thermal expansion.
[0008] Based on the above problems, this invention introduces an entropy regulation strategy, which combines the hardness difference and thermal expansion coefficient difference of medium / high entropy carbides with different entropy levels in different configurations, and applies it to the design and preparation of five-layer symmetric gradient ceramic cutting tool materials, thus developing a gradient ceramic cutting tool material with both high hardness and high toughness.
[0009] Currently, there is no research on constructing medium-to-high entropy composite toughened alumina gradient ceramic cutting tools by combining medium / high entropy carbides with dual-phase high entropy alloys using entropy control strategies. Summary of the Invention
[0010] To address the shortcomings of existing technologies, this invention provides a medium-to-high entropy composite hardening and toughening gradient ceramic cutting tool material with high hardness and high toughness, along with a method for preparing and applying this ceramic cutting tool material. This invention achieves efficient synergistic hardening and toughening of alumina ceramics by rationally designing the gradient structure through an entropy regulation strategy, introducing residual compressive stress on the surface to ensure high hardness, and guaranteeing high toughness internally.
[0011] In a first aspect, the present invention provides an entropy-controlled, medium-to-high entropy composite toughening gradient ceramic cutting tool material, the material having a five-layer gradient structure, wherein the first layer is a pentagonal gradient layer, the second layer is a quaternary gradient layer, the third layer is a ternary gradient layer, the fourth layer is a quaternary gradient layer, and the fifth layer is a pentagonal gradient layer; the pentagonal gradient layer comprises the following components: alumina, a pentagonal high-entropy alloy, and a pentagonal high-entropy carbide; the quaternary gradient layer comprises the following components: alumina, a pentagonal high-entropy alloy, and a quaternary high-entropy carbide; and the ternary gradient layer comprises the following components: alumina, a pentagonal high-entropy alloy, and a ternary medium-entropy carbide.
[0012] The following are further preferred options among the above materials.
[0013] Each of the five gradient layers has the same thickness.
[0014] In the pentagonal gradient layer, based on 100 parts by mass, alumina powder comprises 58-64 parts, pentagonal high-entropy alloy powder comprises 8-10 parts, and the remainder comprises pentagonal high-entropy carbide powder; in the quaternary gradient layer, based on 100 parts by mass, alumina powder comprises 58-64 parts, pentagonal high-entropy alloy powder comprises 8-10 parts, and the remainder comprises quaternary high-entropy carbide powder; in the ternary gradient layer, based on 100 parts by mass, alumina powder comprises 58-64 parts, pentagonal high-entropy alloy powder comprises 8-10 parts, and the remainder comprises ternary medium-entropy carbide powder.
[0015] The pentagonal high-entropy alloy is a high-entropy alloy of five elements with atomic ratios of Al, Co, Cr, Fe, and Ni. This pentagonal high-entropy alloy is a dual-phase high-entropy alloy with both body-centered cubic and face-centered cubic structures, so that the ceramic cutting tool material simultaneously contains both body-centered cubic and face-centered cubic structures.
[0016] The five-element high-entropy carbides are high-entropy carbides with atomic ratios of HfC, NbC, TaC, TiC, and ZrC; the four-element high-entropy carbides are high-entropy carbides with atomic ratios of HfC, TaC, TiC, and ZrC; and the three-element medium-entropy carbides are medium-entropy carbides with atomic ratios of HfC, TiC, and ZrC.
[0017] This invention achieves a breakthrough improvement in the mechanical properties of ceramic cutting tools through entropy regulation and a high-entropy composite toughening gradient structure design. First, the surface layer uses a pentagonal high-entropy carbide (HfNbTaTiZr)C with high hardness and low thermal expansion coefficient. During sintering and cooling, residual compressive stress is introduced on the surface due to the mismatch in thermal expansion coefficients with the internal layers. This compressive stress effectively inhibits the initiation and propagation of surface cracks, significantly improving the material's fracture resistance. The interior layer uses a ternary medium-entropy carbide (HfZrTi)C with a relatively high thermal expansion coefficient and relatively low hardness. Second, the gradient transition in composition and properties between layers effectively alleviates the interfacial residual stress caused by the mismatch in interlayer thermal expansion coefficients, avoiding interlayer cracking and delamination, and ensuring the integrity and stability of the gradient structure. Furthermore, the uniform distribution of the AlCoCrFeNi pentagonal high-entropy alloy toughening phase in each layer provides multiple toughening mechanisms, including crack deflection and plastic deformation, further enhancing the overall toughness of the material. Through an optimized spark plasma sintering process, a novel gradient ceramic tool material with both high hardness and excellent fracture toughness was finally obtained, providing a new technical approach for the design of high-performance ceramic tools.
[0018] A second aspect of the present invention provides a method for preparing the above-mentioned entropy-controlled medium-to-high entropy composite toughening gradient ceramic cutting tool material, comprising the following steps:
[0019] (1) Preparation of pentagonal high-entropy alloy powder:
[0020] a. Powders of five elements, Al, Co, Cr, Fe and Ni, are ultrasonically dispersed and ball-milled in a solvent containing a dispersant at an equiatomic ratio to obtain a uniform slurry;
[0021] b. The obtained slurry is dried and sieved to obtain pentagonal high-entropy alloy powder;
[0022] (2) Synthesis of ternary medium-entropy carbide powder and quaternary and pentagonal high-entropy carbide powder:
[0023] a. Five carbides with atomic ratios of HfC, NbC, TaC, TiC and ZrC, four carbides with atomic ratios of HfC, TaC, TiC and ZrC, and three carbides with atomic ratios of HfC, TiC and ZrC were ultrasonically dispersed and ball-milled in solvents containing dispersants to obtain ternary slurries, quaternary slurries and pentagonal slurries;
[0024] b. The ternary slurry, quaternary slurry, and pentagonal slurry are dried and sieved to obtain ternary medium-entropy carbide powder, quaternary high-entropy carbide powder, and pentagonal high-entropy carbide powder, respectively.
[0025] (3) Preparation of each composite powder:
[0026] a. Weigh out 58-64 parts of alumina powder, 8-10 parts of pentagonal high-entropy alloy powder, and the remainder of ternary medium-entropy carbide powder, quaternary high-entropy carbide powder, or pentagonal high-entropy carbide powder per 100 parts by mass.
[0027] b. Pretreatment of alumina powder in a solvent containing a dispersant;
[0028] c. Add pentagonal high-entropy alloy powder, ternary medium-entropy carbide powder, quaternary high-entropy carbide powder or pentagonal high-entropy carbide powder to the solvent, and perform ultrasonic dispersion and ball milling to obtain ternary composite slurry, quaternary composite slurry or pentagonal composite slurry;
[0029] d. The obtained composite slurries are dried and sieved to obtain ternary composite powder, quaternary composite powder or pentaneous composite powder;
[0030] (4) Laying of a five-layer gradient structure:
[0031] Five-element composite powder, quaternary composite powder, ternary composite powder and quaternary composite powder are laid layer by layer to form a five-layer gradient structure;
[0032] (5) Spark plasma sintering:
[0033] The five-layer gradient structure was subjected to discharge plasma sintering under vacuum. The material was densified by controlling the temperature, pressure and holding time. Then it was cooled to room temperature to obtain an entropy-controlled medium-high entropy composite toughened gradient ceramic cutting tool material.
[0034] The above preparation method is further preferred as follows.
[0035] In step (1)a, the particle size of the five element powders Al, Co, Cr, Fe and Ni is 0.5-2μm and the purity is ≥99.9%.
[0036] In step (2)a, the particle size of HfC, NbC, TaC, TiC and ZrC is 0.5-2μm and the purity is ≥99.9%.
[0037] In step (3)a, the alumina powder has a particle size of 0.5-2 μm and a purity of ≥99.9%.
[0038] The dispersant in steps (1)a, (2)a and (3)b is a mixture of polyethylene glycol and polyvinylpyrrolidone in equal proportions, the solvent is anhydrous ethanol, and the mass of the dispersant is 1% of the required mass of the dispersant.
[0039] The ultrasonic dispersion time in steps (1)a, (2)a and (3)c is 10-20 minutes.
[0040] The ball milling in steps (1)a, (2)a and (3)c is a planetary ball milling at a speed of 200-300 rpm for 20-30 hours.
[0041] In step (3)c, pentagonal high-entropy alloy powder, ternary medium-entropy carbide powder, quaternary high-entropy carbide powder or pentagonal high-entropy carbide powder are added. After each addition, ultrasonic dispersion and ball milling are performed in the solvent, and the ultrasonic dispersion time is 10-20 minutes each time.
[0042] In step (4), each of the five gradient structures has the same thickness.
[0043] In step (5), the temperature of the discharge plasma sintering is 1650-1700℃, the pressure is 35-45MPa, and the holding time is 10-15 minutes; the temperature is reduced to 600℃ at a cooling rate of 90-100℃ per minute, and then naturally cooled to room temperature.
[0044] The entropy-controlled medium-to-high entropy composite toughened gradient ceramic tool material prepared by the above method has high hardness, high fracture toughness and excellent wear resistance, which can meet the stringent requirements of high-speed cutting conditions for tool materials.
[0045] Based on this, a third aspect of the present invention provides an application of the above-mentioned entropy-controlled medium-high entropy composite toughening gradient ceramic tool material for preparing high-speed cutting tools.
[0046] This invention has the following technical features and effects:
[0047] 1. This invention introduces entropy regulation strategy and gradient structure design into the alumina-based ceramic cutting tool material system, constructing a five-layer symmetrical gradient structure. The surface layer uses a pentagonal high-entropy carbide (HfNbTaTiZr)C with low thermal expansion coefficient and high hardness. During sintering and cooling, residual compressive stress is introduced into the surface layer due to the mismatch in thermal expansion coefficient, which can effectively inhibit the initiation and propagation of surface cracks. The middle layer uses a quaternary high-entropy carbide (HfTaZrTi)C with moderate performance to achieve a smooth transition in performance. The inner layer uses a ternary medium-entropy carbide (HfZrTi)C with high thermal expansion coefficient and relatively low hardness. Combined with the toughening effect of the AlCoCrFeNi pentagonal equiatomic ratio high-entropy alloy, the overall fracture toughness of the material is effectively improved. Through entropy regulation, the synergistic effect of the dual gradient design is achieved, realizing the simultaneous improvement of material hardness and toughness, i.e., medium-high entropy composite toughening.
[0048] 2. The entropy-controlled medium-high entropy composite toughening gradient ceramic tool material prepared by this invention maintains the high hardness of the alumina matrix, and its hardness and fracture toughness are significantly improved compared with pure alumina ceramic and homogeneous control samples, which fully meets the stringent requirements of high hardness, high toughness and high reliability of tool materials in high-speed cutting conditions.
[0049] 3. The entropy-controlled medium-high entropy composite toughening gradient ceramic cutting tool material of the present invention has a simple process, is conducive to large-scale preparation, and is very suitable for industrial production. Attached Figure Description
[0050] Figure 1 The image shows the fracture morphology of the entropy-controlled medium-high entropy composite toughening gradient ceramic cutting tool material prepared in Example 1. Detailed Implementation
[0051] Prepare the following ingredients:
[0052] Powders containing five elements: Al, Co, Cr, Fe, and Ni, with particle sizes ranging from 0.5 to 2 μm and a purity of ≥99.9%.
[0053] Five types of carbide powders, namely HfC, NbC, TaC, TiC and ZrC, with a particle size of 0.5-2μm and a purity of ≥99.9%.
[0054] Alumina powder with a particle size of 0.5-2μm and a purity of ≥99.9%.
[0055] Solvent containing dispersant: The dispersant is a mixture of polyethylene glycol and polyvinylpyrrolidone in equal proportions, the solvent is anhydrous ethanol, and the mass of the dispersant is 1% of the mass of the powder to be dispersed.
[0056] Example 1
[0057] (1) Preparation of pentagonal high-entropy alloy powder:
[0058] After weighing Al, Co, Cr, Fe and Ni powders in equal atomic ratios, they were placed in a solvent containing a dispersant (the mass of the dispersant was 1% of the mass of the five element powders) and ultrasonically dispersed for 15 minutes. The resulting slurry was then homogenized by planetary ball milling at 300 rpm for 24 hours in a ball mill jar. After drying and sieving, pentagonal high-entropy alloy powder was obtained.
[0059] (2) Synthesis of ternary medium-entropy carbide powder and quaternary and pentagonal high-entropy carbide powder:
[0060] Five carbide powders of HfC, NbC, TaC, TiC and ZrC with equiatomic ratios were weighed and placed in a solvent containing a dispersant (the mass of the dispersant was 1% of the mass of the five carbide powders) for ultrasonic dispersion for 15 minutes. The resulting slurry was then homogenized by planetary ball milling at 300 rpm in a ball mill jar for 24 hours. After drying and sieving, pentagonal high-entropy carbide powder was obtained.
[0061] Weigh out equal atomic ratios of four carbide powders: HfC, TaC, TiC, and ZrC, and obtain quaternary high-entropy carbide powders according to the above process.
[0062] Weigh out equal atomic ratios of three carbide powders: HfC, TiC, and ZrC, and obtain ternary medium-entropy carbide powders according to the above process.
[0063] (3) Preparation of each composite powder:
[0064] Weigh out 62 parts by weight of alumina powder, 8 parts by weight of pentagonal high-entropy alloy powder, and 30 parts by weight of ternary medium-entropy carbide powder. Sonicate the alumina powder in a solvent containing a dispersant (1% of the alumina powder mass) for 15 minutes. Add the pentagonal high-entropy alloy powder to the solvent and continue ultrasonic dispersion for 15 minutes. Add the ternary medium-entropy carbide powder and continue ultrasonic dispersion for 15 minutes. Homogenize the resulting slurry by planetary ball milling at 300 rpm for 24 hours. After drying and sieving, obtain the ternary composite powder.
[0065] Weigh out 62 parts of alumina powder, 8 parts of pentagonal high-entropy alloy powder, and 30 parts of quaternary high-entropy carbide powder per 100 parts by mass. Obtain quaternary composite powder by following the above process.
[0066] Weigh out 62 parts of alumina powder, 8 parts of pentagonal high-entropy alloy powder, and 30 parts of pentagonal high-entropy carbide powder per 100 parts by mass. Obtain the pentagonal composite powder by following the above process.
[0067] (4) Laying of a five-layer gradient structure:
[0068] (5) The composite powder obtained in step (3) is laid layer by layer in a graphite mold according to a five-layer symmetrical gradient structure. The first layer is a pentagonal composite powder, the second layer is a quaternary composite powder, the third layer is a ternary composite powder, the fourth layer is a quaternary composite powder, and the fifth layer is a pentagonal composite powder. Each layer has the same thickness.
[0069] (5) Spark plasma sintering:
[0070] The graphite mold was densified by spark plasma sintering: it was held at 1650℃ and 40MPa for 10 minutes, and then the cooling rate was controlled at 90-100℃ per minute. After the temperature dropped to 600℃, it was naturally cooled to room temperature to obtain a medium-high entropy composite toughened gradient ceramic cutting tool material with entropy regulation.
[0071] After the sintering process is completed, a high-hardness, high-toughness, entropy-controlled, medium-to-high entropy composite toughening gradient ceramic cutting tool material is obtained. Its mechanical properties are: Vickers hardness 18.68 GPa, fracture toughness 7.95 MPa·m. 1 / 2 .
[0072] Comparative Example 1
[0073] The difference from Example 1 is that a homogeneous structure is adopted, which contains only five-element composite powder and has no gradient structure.
[0074] The mechanical properties of the alumina-high-entropy alloy-pentabyte high-entropy carbide ceramic cutting tool material obtained after sintering according to step (5) are: Vickers hardness 17.40 GPa, fracture toughness 6.28 MPa·m 1 / 2 .
[0075] Comparative Example 2
[0076] The difference from Example 1 is that a homogeneous structure is used, containing only quaternary composite powder, without a gradient structure.
[0077] The mechanical properties of the alumina-high-entropy alloy-quaternary high-entropy carbide ceramic cutting tool material obtained after sintering according to step (5) are: Vickers hardness 16.34 GPa, fracture toughness 6.50 MPa·m 1 / 2 .
[0078] Comparative Example 3
[0079] The difference from Example 1 is that a homogeneous structure is used, containing only ternary composite powder, without a gradient structure.
[0080] The mechanical properties of the alumina-high-entropy alloy-ternary medium-entropy carbide ceramic cutting tool material obtained after sintering according to step (5) are: Vickers hardness 16.12 GPa, fracture toughness 6.79 MPa·m 1 / 2 .
[0081] Example 2
[0082] The difference between this embodiment and Embodiment 1 is that:
[0083] The ultrasonic dispersion time in steps (1), (2) and (3) is 10 minutes.
[0084] The ball milling in steps (1), (2) and (3) is a planetary ball milling at 200 rpm for 30 hours.
[0085] In step (3), the alumina powder in each composite powder is 58 parts, the pentagonal high-entropy alloy powder is 10 parts, and the ternary medium-entropy carbide powder, quaternary high-entropy carbide powder or pentagonal high-entropy carbide powder is 32 parts.
[0086] In step (5), the temperature of the discharge plasma sintering is 1680℃, the pressure is 35MPa, and the holding time is 15 minutes.
[0087] Example 3
[0088] The difference between this embodiment and Embodiment 1 is that:
[0089] The ultrasonic dispersion time in steps (1), (2) and (3) is 20 minutes.
[0090] The ball milling in steps (1), (2) and (3) is a planetary ball milling at 250 rpm for 20 hours.
[0091] In step (3), the alumina powder in each composite powder is 64 parts, the pentagonal high-entropy alloy powder is 9 parts, and the ternary medium-entropy carbide powder, quaternary high-entropy carbide powder or pentagonal high-entropy carbide powder is 27 parts.
[0092] In step (5), the temperature of the discharge plasma sintering is 1700℃, the pressure is 45MPa, and the holding time is 12 minutes.
Claims
1. An entropy-controlled, high-entropy composite toughening gradient ceramic cutting tool material, characterized in that: It has a five-layer gradient structure: the first layer is a pentagonal gradient layer, the second layer is a quaternary gradient layer, the third layer is a ternary gradient layer, the fourth layer is a quaternary gradient layer, and the fifth layer is a pentagonal gradient layer; the pentagonal gradient layer includes the following components: Alumina, a pentagonal high-entropy alloy, and a pentagonal high-entropy carbide; the quaternary gradient layer comprises the following components: Alumina, a pentagonal high-entropy alloy, and a quaternary high-entropy carbide, wherein the ternary gradient layer comprises the following components: Alumina, pentagonal high-entropy alloys and ternary medium-entropy carbides.
2. The entropy-controlled medium-to-high entropy composite toughening gradient ceramic cutting tool material according to claim 1, characterized in that: In the pentagonal gradient layer, based on 100 parts by mass, alumina comprises 58-64 parts, pentagonal high-entropy alloy comprises 8-10 parts, and the remainder comprises pentagonal high-entropy carbides; in the quaternary gradient layer, based on 100 parts by mass, alumina comprises 58-64 parts, pentagonal high-entropy alloy comprises 8-10 parts, and the remainder comprises quaternary high-entropy carbides; in the ternary gradient layer, based on 100 parts by mass, alumina comprises 58-64 parts, pentagonal high-entropy alloy comprises 8-10 parts, and the remainder comprises ternary medium-entropy carbides.
3. The entropy-controlled medium-to-high entropy composite toughening gradient ceramic cutting tool material according to claim 1 or 2, characterized in that: The five-element high-entropy alloy is a five-element high-entropy alloy with atomic ratios of Al, Co, Cr, Fe, and Ni; the five-element high-entropy carbide is a high-entropy carbide with atomic ratios of HfC, NbC, TaC, TiC, and ZrC; the four-element high-entropy carbide is a high-entropy carbide with atomic ratios of HfC, TaC, TiC, and ZrC; and the ternary medium-entropy carbide is a medium-entropy carbide with atomic ratios of HfC, TiC, and ZrC.
4. A method for preparing an entropy-controlled, high-entropy composite toughening gradient ceramic cutting tool material as described in any one of claims 1-3, characterized in that, Includes the following steps: (1) Preparation of pentagonal high-entropy alloy powder: a. Powders of five elements, Al, Co, Cr, Fe and Ni, are ultrasonically dispersed and ball-milled in a solvent containing a dispersant at an equiatomic ratio to obtain a uniform slurry; b. The obtained slurry is dried and sieved to obtain pentagonal high-entropy alloy powder; (2) Synthesis of ternary medium-entropy carbide, quaternary high-entropy carbide and pentaneous high-entropy carbide powders: a. Five carbides with atomic ratios of HfC, NbC, TaC, TiC and ZrC, four carbides with atomic ratios of HfC, TaC, TiC and ZrC, and three carbides with atomic ratios of HfC, TiC and ZrC were ultrasonically dispersed and ball-milled in solvents containing dispersants to obtain ternary slurries, quaternary slurries and pentagonal slurries; b. The ternary slurry, quaternary slurry, and pentagonal slurry are dried and sieved to obtain ternary medium-entropy carbide powder, quaternary high-entropy carbide powder, and pentagonal high-entropy carbide powder, respectively. (3) Preparation of each composite powder: a. Weigh out 58-64 parts of alumina powder, 8-10 parts of pentagonal high-entropy alloy powder, and the remainder of ternary medium-entropy carbide powder, quaternary high-entropy carbide powder, or pentagonal high-entropy carbide powder per 100 parts by mass. b. Pretreatment of alumina powder in a solvent containing a dispersant; c. Add pentagonal high-entropy alloy powder, ternary medium-entropy carbide, quaternary high-entropy carbide or pentagonal high-entropy carbide powder to the solvent, and perform ultrasonic dispersion and ball milling to obtain ternary composite slurry, quaternary composite slurry or pentagonal composite slurry; d. The obtained slurries are dried and sieved to obtain ternary composite powder, quaternary composite powder or pentaneous composite powder; (4) Laying of a five-layer gradient structure: Five-element composite powder, quaternary composite powder, ternary composite powder and quaternary composite powder are laid layer by layer to form a five-layer gradient structure; (5) Spark plasma sintering: The five-layer gradient structure was subjected to discharge plasma sintering under vacuum. The material was densified by controlling the temperature, pressure and holding time. Then it was cooled to room temperature to obtain an entropy-controlled medium-high entropy composite toughened gradient ceramic cutting tool material.
5. The method for preparing entropy-controlled medium-to-high entropy composite toughening gradient ceramic cutting tool material according to claim 4, characterized in that, In step (1)a, the particle size of the five element powders Al, Co, Cr, Fe and Ni is 0.5-2 μm and the purity is ≥99.9%; in step (2)a, the particle size of HfC, NbC, TaC, TiC and ZrC is 0.5-2 μm and the purity is ≥99.9%; in step (3)a, the particle size of alumina powder is 0.5-2 μm and the purity is ≥99.9%.
6. The method for preparing entropy-controlled medium-to-high entropy composite toughening gradient ceramic cutting tool material according to claim 4, characterized in that, The ultrasonic dispersion time in steps (1)a, (2)a and (3)c is 10-20 minutes; the ball milling is performed by planetary ball milling at a speed of 200-300 rpm for 20-30 hours.
7. The method for preparing entropy-controlled medium-to-high entropy composite toughening gradient ceramic cutting tool material according to claim 4, characterized in that, The dispersant in steps (1)a, (2)a and (3)b is a mixture of polyethylene glycol and polyvinylpyrrolidone in equal proportions, and the solvent is anhydrous ethanol; the mass of the dispersant is 1% of the required mass of the dispersant.
8. The method for preparing entropy-controlled medium-to-high entropy composite toughening gradient ceramic cutting tool material according to claim 4, characterized in that, In step (3)c, pentagonal high-entropy alloy powder, ternary medium-entropy carbide, quaternary high-entropy carbide or pentagonal high-entropy carbide powder are added. After each addition, ultrasonic dispersion and ball milling are performed in the solvent, and the ultrasonic dispersion time is 10-20 minutes each time.
9. The method for preparing entropy-controlled medium-to-high entropy composite toughening gradient ceramic cutting tool material according to claim 4, characterized in that, In step (5), the temperature of the discharge plasma sintering is 1650-1700℃, the pressure is 35-45MPa, and the holding time is 10-15 minutes; the temperature is reduced to 600℃ at a cooling rate of 90-100℃ per minute, and then naturally cooled to room temperature.
10. The application of the entropy-controlled medium-to-high entropy composite toughening gradient ceramic cutting tool material according to any one of claims 1-3, characterized in that, Used to manufacture high-speed cutting tools.